Effects of sub-chronic exposure to atmospheric PM2.5 on fibrosis, inflammation, endoplasmic reticulum stress and apoptosis in the livers of rats. Issue 2 (6th February 2018) - Li, Ruijin; Zhang, Mei; Wang, Ying; Yung, Ken Kin Lam; Su, Ruijun; Li, Zhuoyu; Zhao, Liping; Dong, Chuan; Cai, Zongwei
Graphical Abstract: Abstract: Epidemiological studies have revealed that exposure to PM2.5 is linked to liver cancer. However, the hepatic toxicity and relevant molecular mechanisms of PM2.5 have not yet been fully described. Herein, we report on our investigation of the fibrosis, inflammation, endoplasmic reticulum (ER) stress and apoptosis in the livers of rats, caused by exposure to PM2.5 during summer and winter in Taiyuan, China. Male SD rats were sub-chronically exposed to PM2.5 (in summer: 0.2, 0.6, 1.5 mg per kg of b.w.; in winter: 0.3, 1.5, 2.7 mg per kg of b.w.) via intratracheal instillation once every 3 days for 60 days. The results showed that exposure to high dosages of PM2.5 caused the following: (1) hepatic histopathological changes and liver function decline through elevating the activities of AST, ALT, CYP450 and GST; (2) triggered liver fibrosis, in which TGF-β1, Col I, Col III, and MMP13 mRNA and protein expression were significantly upregulated, and enhanced inflammation with the overexpression of TNF-α, IL-6 and HO-1 versus the control; (3) induced liver ER stress and cell apoptosis via activating the GRP78/ATF6/CHOP/TRB3/caspase 12 pathway. The data also indicated that the liver injury induced by winter PM2.5 in Taiyuan was more serious compared to that induced by summer PM2.5 . This work provides new insight into the mechanisms of PM2.5 -induced liver injury, and aids the understanding of the underlying mechanisms by which PM2.5 might affect liver diseases.